High titre neutralizing antibodies in response to SARS–CoV–2 infection require RBD–specific CD4 T cells that include proliferative memory cells - Phetsouphanh, Chansavath; Khoo, Weng Hua; Jackson, Katherine; Klemm, Vera; Howe, Annett; Aggarwal, Anupriya; Akerman, Anouschka; Milogiannakis, Vanessa; Stella, Alberto Ospina; Rouet, Romain; Schofield, Peter; Faulks, Megan L.; et al. (Frontiers in Immunology, 2022)
Background: Long-term immunity to SARS-CoV-2 infection, including neutralizing antibodies and T cell-mediated immunity, is required in a very large majority of the population in order to reduce ongoing disease burden. Methods: We have investigated the association between memory CD4 and CD8 T cells and levels of neutralizing antibodies in convalescent COVID-19 subjects. Findings: Higher titres of convalescent neutralizing antibodies were associated with significantly higher levels of RBD-specific CD4 T cells, including specific memory cells that proliferated vigorously in vitro. Conversely, up to half of convalescent individuals had low neutralizing antibody titres together with a lack of receptor binding domain (RBD)-specific memory CD4 T cells. These low antibody subjects had other, non-RBD, spike-specific CD4 T cells, but with more of an inhibitory Foxp3+ and CTLA-4+ cell phenotype, in contrast to the effector T-bet+, cytotoxic granzymes+ and perforin+ cells seen in RBD-specific memory CD4 T cells from high antibody subjects. Single cell transcriptomics of antigen-specific CD4+ T cells from high antibody subjects similarly revealed heterogenous RBD-specific CD4+ T cells that comprised central memory, transitional memory and Tregs, as well as cytotoxic clusters containing diverse TCR repertoires, in individuals with high antibody levels. However, vaccination of low antibody convalescent individuals led to a slight but significant improvement in RBD-specific memory CD4 T cells and increased neutralizing antibody titres. Interpretation: Our results suggest that targeting CD4 T cell epitopes proximal to and within the RBD-region should be prioritized in booster vaccines.